A Web-Based Student Learning Outcome Assessment System for Secondary Education: Design, Development, and Empirical Evaluation - Ryan Sadhana; Alexandre Freire (Ceddi Journal of Education, 2025)
Student learning outcome assessment is an essential component in ensuring the quality of learning and accountability in secondary education. However, in practice, many schools still implement fragmented, semi-manual assessment systems, resulting in low efficiency, poor data accuracy, and limited pedagogical use of assessment results. This study aims to design, develop, and empirically evaluate an integrated web-based student learning outcome assessment system to support assessment management in secondary schools. The study used a mixed-methods approach, combining qualitative system development and quantitative evaluation. The system was developed using the Waterfall model and Unified Modeling Language (UML). Empirical evaluation was conducted through system trials with 20 students as end users and validation by media, information technology, and language experts. Quantitative data were analyzed descriptively, while qualitative data were analyzed thematically. The results show that the developed system has a very high level of feasibility in terms of usability, functional reliability, and language clarity, and can improve assessment management efficiency while minimizing data inconsistencies. These findings have global implications for the development of efficient and sustainable digital assessment systems, particularly in developing countries with limited resources and varying levels of technological readiness.